The Threat of Discontinuity Ancient Scripts in the Islamic-Malay Manuscript - Kalsum, Nyimas Umi; Rachmadini, Naffa (Arabiyatuna: Jurnal Bahasa Arab, 2023)
The purpose of this writing is to prove that there is a threat of discontinuity of ancient scripts in Malay Islamic manuscripts. Preservation of cultural heritage in the form of ancient script tends to be ignored. Abandonment of ancient scripts in the form of discontinuity the inheritance of ancient scripts; discontinuity of ancient script writing and discontinuity due to myths. In fact, these three aspects have the effect of threatening the discontinuity of ancient script. Through direct and indirect observation of digital collections of ancient manuscripts and free interviews with informants consisting of government agencies, traditional leaders and communities of ancient script lovers. Three ancient scripts that are threatened with discontinuity were found: (1) Jawi script, (2) Ulu script and (3) Lontaraq script. To then do data analysis by means of descriptive, interpretive and reflective of the existing data. This research shows that the government's policy regarding the preservation of cultural heritage must be handed down by the local government in an effort to preserve ancient scripts with outreach, workshops/training as a condition for the sustainability of cultural heritage. In addition, recruitment of ancient script experts is needed to increase qualified human resources and ancient script experts so that local content subjects can be realized. This is important to increase the preservation of ancient scripts.Â